On a functional differential inclusion - CERNEA, Aurelian (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
We consider a Cauchy problem associated to a nonconvex functional di erential inclusion and we prove a Filippov type existence result. This result allows to obtain a relaxation theorem for the problem considered. Mathematics Subject Classification (2010): 34A60, 34K05, 34K15, 47H10.